THE PHILOSOPHY OF LANGUAGE IN AL-FARĀBĪ’S THOUGHT: BETWEEN LOGIC, SYMBOL, AND REASONING - Mardani, Dadan; Hezam, Motea Naji Dabwan; Mahmud, Mahmud; Rohanda, Rohanda (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
Al-Farābī’s contributions to Islamic philosophy extend deeply into the philosophy of language, yet scholarly attention to this dimension remains limited. This study re-examines al-Farābī’s linguistic philosophy by focusing on three interrelated dimensions: logic, symbol, and reasoning. The background of the research lies in the need to reassess classical frameworks in light of contemporary debates on language, cognition, and meaning, where non-Western traditions remain underrepresented. The objective is to explicate how al-Farābī conceptualizes language not merely as a communicative tool, but as an epistemic system for organizing rational thought and symbolic representation. Using a qualitative method, the study employs textual-philosophical analysis of al-Farābī’s major works, including Kitāb al-Ḥurūf, Kitāb al-Alfāẓ al-Musta‘mala fī al-Manṭiq, and his commentary on De Interpretatione, supported by recent scholarly findings. The results reveal that al-Farābī understands language as a structured expression of the intellect, capable of conveying both demonstrative propositions and imaginative constructs. His classification of syllogisms into demonstrative, dialectical, rhetorical, poetic, and sophistical shows the multiplicity of language functions, each with distinct epistemological and moral purposes. Furthermore, his reflections on metaphor, rhetoric, and prophetic discourse demonstrate the cognitive and ethical role of symbolic language in shaping society and cultivating virtue. The study concludes that al-Farābī’s philosophy of language integrates logical rigor with symbolic depth, offering an early model of semiotic realism in which words, concepts, and referents form a triadic relationship grounded in reason and truth. This synthesis provides a foundational contribution to the Islamic intellectual tradition while also enriching contemporary philosophy of language, hermeneutics, and intercultural dialogue.